Moving with risk: Forced displacement and vulnerability to hazards in Colombia. (August 2021) - Few, Roger; Ramírez, Viviana; Armijos, Maria Teresa; Hernández, Lina Andrea Zambrano; Marsh, Hazel
Highlights: Analyses vulnerability to hazards as a consequence of forced displacement. Explores the experiences and perspectives of displaced people in Colombia. Reveals how resettlement and risk reflect their ongoing marginalisation. Multiple structural barriers limit people's engagement in disaster risk reduction. Potential exists for more flexible and creative approaches to risk management. Abstract: The paper examines the processes through which people forced from their homes by conflict can become exposed to heightened risk from environmental hazards in the places where they resettle. It reports on research undertaken with internally displaced people who moved to informal settlements in four locations in Colombia. With one of the world's largest displaced populations and a high annual incidence of hazard events such as landslides and floods, enabling people to create a durable sense of security in their places of resettlement is a major development challenge for the country. However, as the testimonies from individual experiences and perspectives makes clear, this problem is not one that can or should be addressed simply by enforcing existing land use and tenure regulations. The study combined qualitative interview methods with arts-based elements designed to facilitate and open up dialogue with research participants. We found that creating a permanent home, however modest, has symbolic meaning that reflects both personal struggle and collective effort: it represents security and stability, even in sites people know are associated with hazards. In tracing how they have interacted with multiple forms of risk, our work shows how displaced people have had to weigh up the threats they face against limited resettlement options, in an ongoing context of marginalisation. For complex reasons, this is a population that tends to be excluded from formal disaster preparedness and mitigation. However, there are indications that this prevailing situation could be challenged, promoting greater flexibility on the part of governmental organisations and enabling communities to become more engaged in disaster risk reduction. In bringing empirical depth to a topic of global significance at the intersection of displacement, disaster and development, we support the call for adaptable approaches to disaster risk management that can support displaced people more effectively and equitably.